1993
DOI: 10.1007/bf00196915
|View full text |Cite
|
Sign up to set email alerts
|

Alamethicin and related peptaibols ? model ion channels

Abstract: Peptaibols are considered as models of those ion channels which consist of a bundle of transbilayer helices surrounding a central pore. X-Ray diffraction and NMR studies have yielded high resolution structures for several peptaibols. In conjunction with other spectroscopic investigations and molecular dynamics simulations, these studies suggest that peptaibols form proline-kinked alpha-helices, and that there may be "hinge-bending" movement of the helix in the region of the central proline residue. The amphipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
170
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(181 citation statements)
references
References 98 publications
10
170
0
1
Order By: Relevance
“…As many as 20 distinguishable conductance states have been described (12). The fluctuations between the stepwise K þ and Cl À conductivities are consistent with the various sizes of the transmembrane channels due to the presence of different oligomeric states of the helix bundles (13,14) (reviewed in (1,2)). It has been suggested that these pore structures may consist of at least three (15), four (1), or even five subunits (16).…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…As many as 20 distinguishable conductance states have been described (12). The fluctuations between the stepwise K þ and Cl À conductivities are consistent with the various sizes of the transmembrane channels due to the presence of different oligomeric states of the helix bundles (13,14) (reviewed in (1,2)). It has been suggested that these pore structures may consist of at least three (15), four (1), or even five subunits (16).…”
Section: Introductionmentioning
confidence: 64%
“…4 d highly dynamic within its own structure but the size of the supramolecular arrangement can also change over time, for example, in electrophysiological single-channel measurements where different levels in conductivity are obtained depending on the detailed experimental conditions (1,16). Indeed, when the peptide/lipid ratio is diminished, smaller oligomers predominate (Fig.…”
Section: Aggregation Model In Popc Membranesmentioning
confidence: 99%
See 3 more Smart Citations